2023
DOI: 10.3390/antibiotics12040672
|View full text |Cite
|
Sign up to set email alerts
|

General Perceptions and Knowledge of Antibiotic Resistance and Antibiotic Use Behavior: A Cross-Sectional Survey of US Adults

Abstract: This study aimed to assess understanding of antibiotic resistance and evaluate antibiotic use themes among the general public. In March 2018, respondents that were ≥21 years old and residing in the United States were recruited from ResearchMatch.org and surveyed to collect data on respondent expectations, knowledge, and opinions regarding prescribing antibiotics and antibiotic resistance. Content analysis was used to code open-ended definitions of antibiotic resistance into central themes. Chi-square tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Hence, there may be some room, even amongst this cohort, to stop pressuring doctors for antibiotics. This would have a high impact at a personal level, as one facet of targetable interactions at the physician–patient interface [ 24 , 25 ] and at the local, Australian level. More so (and beyond the scope of this study) would be the opportunity to spread the message across parents and pet owners not to seek antibiotics unnecessarily for children and animals in their care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there may be some room, even amongst this cohort, to stop pressuring doctors for antibiotics. This would have a high impact at a personal level, as one facet of targetable interactions at the physician–patient interface [ 24 , 25 ] and at the local, Australian level. More so (and beyond the scope of this study) would be the opportunity to spread the message across parents and pet owners not to seek antibiotics unnecessarily for children and animals in their care.…”
Section: Discussionmentioning
confidence: 99%
“…This receptivity reflects the fact that consumers commented that, despite previously knowing little about the topic, they felt it was important. Encouragingly, research has shown that increased understanding of AMR does correlate with decreased inappropriate use of antibiotics, underscoring the value of targeted education campaigns [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improving health literacy plays a critical role at this point. In Turkey, Syrian immigrants can access health services free of charge [42]. In addition, health services are provided to these immigrants by Syrian healthcare professionals through reinforced immigrant health centers.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, awareness campaigns [70,71], surveys [72], and technological integration in work [73,74] and learning [75,76] environments are crucial to stop an otherwise announced disastrous, unstoppable plague: communication is the key to unified, efficacious actions, especially when the enemy to defeat is so protean, diffused, and challenging.…”
Section: Polymixinsmentioning
confidence: 99%